Model Pengendapan Reservoar Gita Interval 34-1, Formasi Talangakar, Lapangan Widuri, Cekungan Asri - heryanti - efendi; DONATUS HENDRA AMIJAYA; JAROT SETYOWIYOTO (Bulletin of Geology, 2018)
Interval 34-1 is the third largest reservoir in Widuri Field, Asri Basin with cumulative production reaching 11 Million Metric Barrels of Oil (MMBO) from Original Oil in Place (OOIP) 31 MMBO. At Interval 34-1, Gita Reservoir, Talangakar Formation, Widuri Field, no thorough facies analysis has been performed on this sandstone reservoir. This research was conducted to find out lithology facies of research area and how to correlate lithology facies with deposition system. The reservoir deposition model in this research will be built through the understanding of lithology facies and settling system so that geology is expected to be close to the actual condition. The data used in this study are core rock analysis data from three wells with a total length of 485 feet, well log data from 7 production wells and 1 exploratory well, petrography and XRD data, biostratigraphy and paleobathymetry data, and map of seismic attribute of acoustic impendance. The first step is to identify the lithofasies and facies associations for the association of the depositional environment. The sandstone reservoir Gita Interval 34-1 is interpreted to consist of four facies associations namely; estuarine point bar, shallow marine, marsh/swamp, and intertidal flat. The second stage is to correlate the well log data stratigraphy to map the facies overlays horizontally. The third step is to integrate secondary data in the form of seismic attribute maps with log correlation and facies association analysis to predict the deposition model of each cycle adjacent to Interval 34-1. Reservoir deposition model Gita Interval 34-1 at the bottom develops supratidal marsh/swamp. Subsequent transgression phases resulted in the deposition of shallow marine deposits, followed by estuary channel deposits in subsequent regression periods. Subsequent transgression produces intertidal flat deposit, followed by shallow marine deposits in subsequent transgression periods. Keywords: Asri Basin, facies, facies associations, depositional model